2005
DOI: 10.1007/s10482-004-7837-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cellular fatty acid profiles of the microbiota in different gut regions of BALB/c and C57BL/6J mice

Abstract: The gastrointestinal tracts of developed animals are colonized by an extremely complex and diverse microbial ecosystem. The host and its microbiota are in close interaction with each other, and the host's genetic characteristics have been suggested to have an influence on the composition of fecal bacteria. However, different sections of gastrointestinal tract harbor microbes typical of each particular section and knowledge of the effect of the host's genotype on the microbiota in the different parts of the gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Our results supported previous findings from mouse and human GI tract analyses (21,51) and from pigs (47) emphasizing that each individual carries a unique intestinal bacterial community, determined primarily by its genotype and secondarily by its environment. Any putative effect of a treatment would therefore need to be determined against this background variation between individual pigs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results supported previous findings from mouse and human GI tract analyses (21,51) and from pigs (47) emphasizing that each individual carries a unique intestinal bacterial community, determined primarily by its genotype and secondarily by its environment. Any putative effect of a treatment would therefore need to be determined against this background variation between individual pigs.…”
Section: Discussionsupporting
confidence: 91%
“…Human twins have more similar intestinal communities than do married couples or unrelated individuals, giving some of the first evidence that genotype is a major contributor to microbial selection in the intestine (51). A later study with mice provides further support for the role genetics plays in microbial diversity (21). Conceivably, the ileum community is under different constraints, due in part to the greater surface-to-volume ratio, the lower bacterial density, and the active nature of the ileal tissue (for example, through excretion of mucus).…”
Section: Discussionmentioning
confidence: 91%
“…A high similarity in gut microbiota composition between monozygotic twins compared to less related or unrelated individuals implies that such differences are associated with the genetic background of the host (Zoetendal et al ., 2001). In inbred mouse strains, the major histocompatibility complex (MHC) haplotype has been implicated in controlling intestinal colonization (Toivanen et al ., 2001; Vaahtovuo et al ., 2001; Jussi et al ., 2005). MHC molecules are expressed on both somatic (MHC class I) and immune cells (MHC class II) and they play a role in antigen presentation (Klein and Sato, 2000a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Further support for genetic factors affecting the composition of the intestinal microbiome comes from studies in humans where specific microbiota profiles were associated with subjects that had mutations at specific gene loci . Similar studies in mice have shown an association of genetic loci with shifts in the gut microbial diversity, suggesting that the host's genetic factors have a strong influence on the composition of the intestinal microbiome as well as its metabolic output …”
Section: Genetic Factors and The Microbiomementioning
confidence: 98%
“…In the colon, the mucus layer is thick (~150 µm) and double‐layered. Although the outer layer has an abundance of microorganisms, the inner layer of mucus is remarkably resistant to penetration and prevents the microbiota from interacting with the lining of the epithelium . The production of intestinal mucus is regulated by the products of intestinal microbiome; germ‐free mice have a highly attenuated mucus layer of the colon despite normal goblet cells, and the addition of bacterial lipopolysaccharide or peptidoglycan causes the release of intestinal mucus by the goblet cells .…”
Section: Genes Involved With Stratification and Compartmentalizationmentioning
confidence: 99%